The law of armed conflict i nternational humanitarian law in war - Solis, Gary D. (Cambridge University Press, 2016)
The Law of Armed Conflict: International Humanitarian Law introduces law students and undergraduates to the law of war in an age of terrorism. What law of armed conflict/international humanitarian law applies to particular armed conflicts? Does that law apply to terrorists as well? What is the status of participants in an armed conflict? What constitutes a war crime? What is a lawful target and how are targeting decisions made? What are rules of engagement? What weapons are lawful and unlawful, and why? This text takes the reader through these essential questions of the law of armed conflict and international humanitarian law to an awareness of finer points of battlefield law. The U.S.-weighted text incorporates lessons from many nations and includes hundreds of cases from jurisdictions worldwide